Literary Devices in Gott hold Ephraim Lessing’s Works - Mamatova Anora Iminovna (Periodica Journal, 2022)
This article shows the main theoretical works of Lessing are written in an acutely polemical form, with tremendous energy and temperament. Lessing's struggle against such enemies as the head of German classicism Gottsched stirred up the ideological life of Germany and helped awaken the progressive democratic minds. In the eyes of Lessing, there is one main criterion for evaluating not only an individual person but also each nation and their service to the progressive ideals of humanity, the ideals of humanism and progress.
Keywords: maintain; preach; evidence of emotional involvement